2021
DOI: 10.3390/v13071271
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Approaches for Cancer Treatment Using Oncolytic Viruses: Projecting the Perspectives through Clinical Trials Outcomes

Abstract: Recent cancer immunotherapy breakthroughs have fundamentally changed oncology and revived the fading hope for a cancer cure. The immune checkpoint inhibitors (ICI) became an indispensable tool for the treatment of many malignant tumors. Alongside ICI, the application of oncolytic viruses in clinical trials is demonstrating encouraging outcomes. Dozens of combinations of oncolytic viruses with conventional radiotherapy and chemotherapy are widely used or studied, but it seems quite complicated to highlight the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 225 publications
1
21
0
1
Order By: Relevance
“…In this context, OVs, particularly genetically engineered OVs, can enhance lymphocyte infiltration and activation as well as lysis of cancer cells. Thus, to overcome this lack of ICI effectiveness in too many patients, OV virotherapy combined with ICIs has been tested in preclinical models and clinical trials, and has shown promising results [ 114 , 115 , 116 , 117 ] OVs that are currently under clinical trials in combination with ICIs are HSV (OH2), VACV (PexaVec), Reovirus (Reolysin), Adenovirus (LOAd703), NDV (MEDI5395), and VSV (VSV-IFNb-NIS) ( Table 3 ). However, recent studies suggest that genetically engineered OVs and OVs expressing immune stimulating cytokines that have greater potential of altering TME have shown enhanced efficacy in combination with ICIs.…”
Section: Combination Therapy With Oncolytic Virusmentioning
confidence: 99%
“…In this context, OVs, particularly genetically engineered OVs, can enhance lymphocyte infiltration and activation as well as lysis of cancer cells. Thus, to overcome this lack of ICI effectiveness in too many patients, OV virotherapy combined with ICIs has been tested in preclinical models and clinical trials, and has shown promising results [ 114 , 115 , 116 , 117 ] OVs that are currently under clinical trials in combination with ICIs are HSV (OH2), VACV (PexaVec), Reovirus (Reolysin), Adenovirus (LOAd703), NDV (MEDI5395), and VSV (VSV-IFNb-NIS) ( Table 3 ). However, recent studies suggest that genetically engineered OVs and OVs expressing immune stimulating cytokines that have greater potential of altering TME have shown enhanced efficacy in combination with ICIs.…”
Section: Combination Therapy With Oncolytic Virusmentioning
confidence: 99%
“…A variety of different oncolytic viruses have been engineered and attenuated, namely the Herpes Simplex virus (HSV), vaccinia virus, myxoma virus, measles, reovirus, vesicular stomatitis virus (VSV), Semliki Forest virus (SFV) and the adenovirus (Ramachandran et al, 2017, Chen et al, 2021, Kangas et al, 2021, Lou et al, 2021, Oosenbrug et al, 2021, Panagioti et al, 2021, Woo et al, 2021. Oncolytic viruses are typically administered in conjunction with chemotherapy and radiation treatments to specifically identify and kill cancer cells (Malogolovkin et al, 2021).…”
Section: Virotherapymentioning
confidence: 99%
“…In the 6 years since talimogene laherparepvec (T-vec, Imlygic) was approved by the FDA for melanoma in 2015, there has not been another FDA approval, either of T-VEC in a second indication or of another virus. However, it remains an active area of investigation, with over 200 ongoing clinical trials of different viruses spanning numerous types of viruses in combination with a variety of other therapies (recently reviewed here [61]). Poor efficacy is thought to be due to a variety of factors including antiviral immune responses, the immunosuppressive tumor microenvironment, and low delivery of systemically administered virus to tumor sites.…”
Section: Oncolytic Virusesmentioning
confidence: 99%